Self-care in children and young people with complex chronic conditions: a qualitative study using Emotional Text Mining - Spitaletta, Giuseppina; Biagioli, Valentina; Greco, Francesca; Mascolo, Rachele; Liburdi, Annachiara; Manzi, Giulia; Gawronski, Orsola; Ricci, Riccardo; Tiozzo, Emanuela; Vellone, Ercole; Grimaldi Capitello, Teresa; Salata, Michele; et al. (Frontiers in Pediatrics, 2023)
Objectives: To explore: 1) self-care behaviors in children and young people (range: 6 months-24 years) with complex chronic conditions, characterized by the diagnosis of a severe chronic condition, substantial family-identified needs, functional limitations associated with technology dependence, and intensive use of healthcare services; 2) the contribution to self-care of family members and other persons involved in the child's health and daily life context (e.g., health professionals and teachers), and 3) the principal factors that might have influenced the self-care process associated with developmental age. Methods: A qualitative descriptive study was conducted in an Italian academic tertiary pediatric hospital between September 2020 and May 2021. Overall, 25 focus groups and 7 online interviews were conducted via videoconferencing. Textual data were analyzed using Emotional Text-Mining, to identify three levels of communication: the factors, the main themes (clusters), and the sub-themes. Results: A total of 104 participants were enrolled, including 27 patients with complex chronic conditions (12 males, mean age=11.1±4.40), 33 parents, 6 siblings, 33 health professionals, and 5 teachers. Participants described the process of self-care through four main factors: 'self-care', 'external settings', 'family', and 'management'. Five clusters (themes) were identified: 1) Self-care management (device; consulting); 2) Shift of agency (influencing factors; parents; school); 3) Self-care support (normal life and personal development; multidisciplinary support); 4) Daily self-care maintenance/monitoring; 5) Treatment adherence. Self-care management was mostly relevant for parents of children aged between 6 months and 3 years.The self-care process varies according to the needs related to the specific developmental age and the evolution of the clinical condition over time. The contribution of the family, health professionals, and social network is fundamental for adequate self-care. To help families manage the unstable condition of their children at home, it is necessary to strengthen the supportive network, implement home care, and ensure continuity of care.